Effects of Labor Epidural Analgesia on Short Term Neonatal Morbidity - Salameh KM; Anvar Paraparambil V; Sarfrazul A; Lina Hussain H; Sajid Thyvilayil S; Samer Mahmoud A (Dove Medical Press, 2020)
Khalil Mohd Salameh, Vellamgot Anvar Paraparambil , Abedin Sarfrazul, Habboub Lina Hussain, Salim Sajid Thyvilayil , Alhoyed Samer Mahmoud Department of Pediatrics and Neonatology, Al Wakra Hospital, Hamad Medical Corporation, Al Wakra, QatarCorrespondence: Khalil Mohd SalamehDepartment of Pediatrics and Neonatology, Al Wakra Hospital, Hamad Medical Corporation, Al Wakra, QatarTel +974 40114258Email Ksalameh@hamad.qaBackground: Epidural Analgesia (EA) is the most effective and most commonly used method for pain relief during labor. Some researchers have observed an association between EA and increased neonatal morbidity. But this observation was not consistent in many other studies.Objectives: The primary objective of the study was to examine whether exposure to epidural analgesia increased the risk of NICU admission. The secondary objectives included the risks of clinical chorioamnionitis, instrumental delivery, neonatal depression, respiratory distress, birth trauma, and neonatal seizure during the first 24 hours of life.Methods: This was a retrospective cohort study involving 2360 low-risk nulliparous women who delivered at AWH, Qatar, during the two years between January 2016 December and 2017. Short-term neonatal outcomes of the mothers who received EA in active labor were compared with a similar population who did not receive EA. As secondary objectives, labor parameters like maternal temperature elevation, duration of the second stage of labor, and instrumental delivery were compared.Results: Significantly higher numbers of neonates were admitted to the NICU from the EA group (P< 0.001, OR 1.89, 95% CI 1.45 to 2.46). They were more likely to have respiratory distress (P=0.01, OR 1.49, 95% CI 1.07 to 2.07), birth injuries (P=0.02, OR =1.71, 95% CI 1.06 to 2.74), admission temperature> 37.5 °C (P= 0.04, OR 3.40, 95% CI 1.00 to 11.49), need for oxygen on the first day (P=0.04, OR 1.44, 95% CI 1.01 to 2.07) and receive antibiotics (P< 0.001, OR 2.06,95% CI 1.47 to 2.79). There was no difference in the Apgar score at 1 minute (P=0.12), need of resuscitation at birth (P=0.05), neonatal white cell count (P=0.34), platelet count (P=0.38) and C reactive protein (P=0.84). Mothers who received EA had a lengthier second stage (P< 0.001), temperature elevation > 37.5°C (P< 0.001, OR 7.40, 95% CI 3.93 to 13.69) and instrumental delivery (P< 0.001, OR 2.13, 95% CI 1.69 to 2.68).Conclusion: EA increases NICU admission, antibiotic exposure, neonatal birth injuries, need for positive pressure ventilation at birth, and respiratory distress in the first 24 hours of life. Mothers on epidural analgesia have prolonged second stage of labor, a higher rate of instrumental delivery, meconium-stained amniotic fluid, fetal distress, and temperature elevation.Keywords: epidural analgesia, neonatal morbidity, NICU admission